Pengaruh Senam Yoga Terhadap Mual Muntah Hamil - Mudlikah, Siti (Universitas Muhammadiyah Gresik, 2023)
ABSTRACT Nausea and vomiting can affect nutritional intake for pregnant women, changes in the pregnancy process increases the hormone estrogen and HCG placenta which stimulates nausea and vomiting in the first trimester, peaking at 9 weeks in the morning. Nausea and vomiting can cause a lack of nutritional intake and have a negative impact on the health of the mother and fetus with pregnancy complications. The nutritional adequacy rate of pregnant women must be met properly so that the fetus can grow and develop properly. The purpose of this study was to determine the effect of yoga exercise on pregnant women's nausea and vomiting The research method uses a cross-sectional approach, the population of first trimester pregnant women in Jatikalang Sidoarjo Village from January to March 2023. The sample of all first trimester pregnant women is 20 people, data collection uses a frequency distribution, data analysis uses the One sample test. Pregnancy exercise data were obtained from observations with checklists and nausea and vomiting data were obtained from interviews using a direct questionnaire instrument. Results: It is known that the characteristics of 20 pregnant women all experienced nausea and vomiting in the category of mild nausea and vomiting by 8 people (45%), moderate nausea and vomiting by 7 people (35%) and severe nausea and vomiting by 4 people (20%). The One-Sample Test analysis obtained a t value (tcount of -416,563. The df value (degrees of freedom) was 19. The Sig (2 tailed) value was 0.000 ≤ 0.05 indicating an average of 75 effectiveness of yoga exercises Conclusion: There is an effect of yoga exercise on nausea and vomiting of pregnant women. Regular and routine yoga exercises can effectively reduce nausea and vomiting in first trimester pregnant women